2020
DOI: 10.1038/s41598-020-65892-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sulfonated ligands on gold nanoparticles as virucidal antiviral for Dengue virus

Abstract: Dengue virus (DENV) causes 390 million infections per year. Infections can be asymptomatic or range from mild fever to severe haemorrhagic fever and shock syndrome. Currently, no effective antivirals or safe universal vaccine is available. In the present work we tested different gold nanoparticles (Aunp) coated with ligands ω-terminated with sugars bearing multiple sulfonate groups. We aimed to identify compounds with antiviral properties due to irreversible (virucidal) rather than reversible (virustatic) inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Gold is extensively used for diagnostic devices and vaccines for being chemically inert and relatively nontoxic [45]. Zacheo and collaborators [46] successfully tested gold nanoparticles (AuNPs) sized 4-5 nm with sulfonated group ligands varying in number, size, orientation and the sugar as head groups against Dengue virus (DENV). With a moderate toxicity and virucidal effect, a complex multi-sulfonated with glucose as head group was found to be the most effective against DENV-2, suggesting that this complex of AuNP interacts with DENV-2 envelope protein, inhibiting the virus permanently.…”
Section: Metal Nanoparticles As Antiviralsmentioning
confidence: 99%
“…Gold is extensively used for diagnostic devices and vaccines for being chemically inert and relatively nontoxic [45]. Zacheo and collaborators [46] successfully tested gold nanoparticles (AuNPs) sized 4-5 nm with sulfonated group ligands varying in number, size, orientation and the sugar as head groups against Dengue virus (DENV). With a moderate toxicity and virucidal effect, a complex multi-sulfonated with glucose as head group was found to be the most effective against DENV-2, suggesting that this complex of AuNP interacts with DENV-2 envelope protein, inhibiting the virus permanently.…”
Section: Metal Nanoparticles As Antiviralsmentioning
confidence: 99%
“…AuNPs with excellent antiviral potential were the one which perfectly fitted the n -octyl-β- d -glucoside binding pocket of envelope protein present in DENV. Thus, presence of surface ligands on AuNPs also influences its antiviral properties (Zacheo et al 2020 ). In another study, similar results have been observed to inhibit interaction between MERS envelope and host cell membrane as represented in Fig.…”
Section: Use Of Nanotechnology For Treating Covid-19mentioning
confidence: 99%
“…Depending on the type and concentration of the third element added [17], the hydrophobicity and electrical properties are the DLC properties that experience the greatest changes [24,35]. In biological terms, the metals that are more interesting regarding their antimicrobial features, including antiviral features, are Ag [49,50,[56][57][58][59], Au [60][61][62][63][64][65][66], and Cr [67][68][69]. Different types of metallic and non-metallic elements can be integrated into the DLC matrix to improve the tribological characteristics due to the lack of reactivity of this coating.…”
Section: Diamond-like Carbonmentioning
confidence: 99%